Investigating the Interplay Between Identity Gaps and Communication Patterns in Predicting Relational Intentions in Families in the United States. (26th April 2018) - Phillips, Kaitlin E; Ledbetter, Andrew M; Soliz, Jordan; Bergquist, Gretchen
Abstract: We tested the degree to which identity gaps mediate the association between family communication patterns and relational intentions. Participants included 498 emerging adults from the United States. Both personal-enacted and relational-communal identity gaps mediated the relationship between conversation and conformity orientation and relational intentions. Moreover, family identification (the extent to which one feels a sense of connection with their family group) moderated the mediation effect, altering the relationship between the personal-enacted and relational-communal identity gaps and relational intentions. Such that, when family identification is low it does not buffer the negative effect of the relational-communal gap, and when it is high, it exacerbates the negative effect of the personal-enacted identity gap on relational intentions. Specifically, the direction of moderating effect of family identification was in opposite directions for these two identity gaps. The only direct effect was a curvilinear relationship between conformity and relational intentions.